A note on model reduction for microelectromechanical systems. (20th December 2016) - Escher, Joachim; Gosselet, Pierre; Lienstromberg, Christina
Abstract: Numerical evidence is provided that there are non-constant permittivity profiles which force solutions to a two-dimensional coupled moving boundary problem modelling microelectromechanical systems to be positive, while the corresponding small-aspect ratio model produces solutions which are always non-positive.